Acylation of Homoatomic Ge9 Cages and Subsequent Decarbonylation. Issue 36 (1st June 2018) - Frischhut, Sabine; Klein, Wilhelm; Drees, Markus; Fässler, Thomas F.
Abstract: The direct acylation of Ge9 Zintl clusters by the reaction of K[Ge9 Si(SiMe3 )3 3 ] with acyl chlorides in hexane or toluene solutions is presented, leading to the neutral, carbonyl‐derivatized products [Si(SiMe3 )3 3 Ge9 (CO)R′] (R′=Me, i Pr, t Bu, Ph, Bz, cyclopropylmethyl, phenethyl, 4‐vinylphenyl). This reaction is applicable to a wide range of acyl chlorides and allows for diverse functionalization of Ge9 Zintl clusters. [Si(SiMe3 )3 3 Ge9 (CO) t Bu] readily releases CO at ambient conditions under formation of [Si(SiMe3 )3 3 Ge9 t Bu]. This temperature‐dependent decarbonylation most likely proceeds via a radical Norrish‐type I α‐bond cleavage. Except for R′= t Bu and Bz all obtained acyl‐derivatized Ge9 cluster compounds do not release CO even at elevated temperatures. All compounds were characterized by NMR spectroscopy. [Si(SiMe3 )3 3 Ge9 (CO)R′] (R′= t Bu, Ph, Me, i Pr) as well as [Si(SiMe3 )3 3 Ge9 t Bu] were further structurally characterized by single crystal X‐ray diffraction. Abstract : A new synthetic strategy for specifically functionalized Ge9 Zintl clusters is presented. A variety of neutral acyl‐derivatized Ge9 Zintl clusters were synthesized by reacting [Si(SiMe3 )3 3 Ge9 ] − with acyl chlorides in hexane or toluene. In particular, the pivaloyl‐functionalized Ge9 cluster eliminates carbon monoxide in solution at room temperature upon radical α‐bond cleavage.